2018
DOI: 10.1080/10245332.2018.1443897
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance 1 (MDR1/ABCB1) gene polymorphism (rs1045642 C > T) and susceptibility to multiple myeloma: a systematic review and meta-analysis

Abstract: This meta-analysis suggests that the MDR1 C > T polymorphism was not associated with the risk of MM. To confirm these findings, further comprehensive and well-designed studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
4
1
Order By: Relevance
“…A similar finding was also found in a study of haplotype involving such polymorphism with the risk of colorectal and esophageal cancer and in a systematic review and meta-analysis regarding the genetic susceptibility to multiple myeloma [27], [41].…”
Section: Resultssupporting
confidence: 84%
“…A similar finding was also found in a study of haplotype involving such polymorphism with the risk of colorectal and esophageal cancer and in a systematic review and meta-analysis regarding the genetic susceptibility to multiple myeloma [27], [41].…”
Section: Resultssupporting
confidence: 84%
“…The identification of new prognostic and predictor factors may help to define subgroups of patients that most likely can benefit from chemotherapy [49]. Among analyzed variants of the ABCB1 gene, including 3435C > T (synonymous variant), 1236C > T (synonymous variant) and 2677G > T/A (non-synonymous variant), the most important seems to be the one located at nucleotide 3435 [50]. It leads to changes at the mRNA level and affects protein folding [51].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have confirmed the relationship of the ABCB1 3435 C > T variant with MM risk. However, published data are still inconclusive [50]. The meta-analysis performed by Razi and co-workers did not find an association of ABCB1 3435C > T with MM susceptibility [50].…”
Section: Discussionmentioning
confidence: 99%
“…A silent mutation at ABCB1 rs1045642 may decrease the expression levels of the mRNA and protein products, or alter the protein structure and substrate affinity (Cascorbi, 2006; Kimchi‐Sarfaty et al, 2007). Genotype TT was found to significantly increase the overall risk of gastric cancer in Iranian individuals and upper aerodigestive tract cancer in Indian individuals (Sabahi et al, 2010; Sam et al, 2007), and was associated with colorectal cancer and multiple myeloma in French individuals (Falkowski et al, 2017; Razi, Anani Sarab, Omidkhoda, & Alizadeh, 2018). There is a correlation between SNPs at rs3789243 with colorectal cancer (Andersen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%